Failure to maintain high-dose treatment regimens during long-term use of zidovudine in patients with symptomatic human immunodeficiency virus type 1 infection. Issue 6 (December 1990) - van Leeuwen, R; van den Hurk, P J; Jöbsis, G J; van der Wouw, P A; Reiss, P; Eeftinck Schattenkerk, J K; Danner, S A; Lange, J M
Abstract : Long-term tolerance of zidovudine treatment was retrospectively analysed in 97 patients with AIDS or AIDS-related complex. After one year of treatment 68% and after two years 87% of the patients had had at least one dose adjustment during their course of therapy. Myelotoxicity was the most common cause (58% of all cases) of dose reductions and therapy interruptions (dose adjustments). At the time of the first dose adjustment 33 patients (34%) were suffering from anaemia (Hb less than 6.0 g/dl), 20 patients (21%) from leukopenia (leukocytes less than 1.5 x 10(9], and 10 patients (10%) from thrombocytopenia (thrombocytes less than 75 x 10(9]. Fifty-six patients (57%) needed one or more blood transfusions during therapy. The median time from the start of therapy to the time of the first dose adjustment was 14 (range: 2-64) weeks in patients who had a first dose adjustment because of anaemia without co-existing leukopenia or thrombocytopenia, and 37 (range: 6-85) weeks in patients who had a first dose adjustment because of leukopenia without co-existing anaemia or thrombocytopenia (p = 0.01). Peripheral blood CD4 positive lymphocyte counts less than or equal to 100/mm3, anaemia, and CDC classification IV-C1 at the start of treatment were associated with a need for an early dose modification or blood transfusion rather than the need for dose modification per se.